Noninvasive ablation of rabbit fetal and placental tissue targets in utero using magnetic resonance‐guided high‐intensity focused ultrasound. (28th March 2019) - Piorkowska, Karolina; Waspe, Adam C.; Wang, Tao; Mougenot, Charles; Ryan, Greg; Drake, James M.; Gerstle, Justin T.
Abstract: Objective: Magnetic resonance‐guided high‐intensity focused ultrasound (MRgHIFU) is a potential noninvasive therapy for fetal conditions. In utero MRgHIFU delivery and proton resonance frequency shift (PRFS) thermometry monitoring will control accuracy of HIFU ablation and confirm in situ tissue heating in a rabbit model. Methods: High‐resolution 3T MR images were acquired in late‐gestation rabbits (approximately 30 days, n = 5). HIFU sonications, using magnetic resonance (MR) thermometry as a guide, were delivered to achieve necrosis in relevant fetal targets. Thermometry, posttreatment magnetic resonance imaging (MRI), and follow‐up histology confirmed ablation. Results: Placentas (n = 14) were treated with 127 ± 34 Wac; thermometry‐indicated temperatures reached 67°C. Lungs (n = 8) were treated with 85 ± 15 Wac and reached 73°C, livers (n = 6) with 80 ± 15 Wac and reached 74°C, and kidneys (n = 5) with 100 Wac and reached 66°C. Histological changes showed focal areas of necrosis with circumferential hemorrhage and/or vasodilation, which transitioned abruptly to healthy tissue. Conclusion: MRgHIFU therapy can effectively target and thermally treat specific in utero organs in this acute fetal rabbit model. PRFS gives in situ temperature control of therapy on tissues. Conceivably, MRgHIFU therapy may be applicable to specific fetal organ anomalies clinically and has the potential to improve the overall fetal outcome over traditional invasive surgical procedures. Abstract : What is already known about this topic? Previous studies using ultrasound guided focused ultrasound have successfully noninvasively ablated fetal placenta in sheep, monkey, and rat models. Preliminary selective fetal reduction studies in rats used focused ultrasound to ablate and stop the heart. What does this study add? This study uses magnetic resonance to add further detail to imaging in utero as well as monitor temperature changes during focused ultrasound ablation. Thorough histology describes pathological changes after treatment.